2013
DOI: 10.1103/physrevb.88.024502
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal correlations in a proximity-coupled normal-metal

Abstract: We report evidence of large, nonlocal correlations between two spatially separated normal metals in superconductor/normal-metal (SN) heterostructures, which manifest themselves as nonlocal voltage generated in response to a driving current. Unlike prior experiments in SN heterostructures, the nonlocal correlations are mediated not by a superconductor, but by a proximity-coupled normal metal. The nonlocal correlations extend over relatively long length scales in comparison to the superconducting case. At very l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…However, this is for a wire with no additional normal metal leads. Experimentally, by measuring the saturation value of I c at low temperatures, we have found that E c is reduced by a fac-tor of about 20 from its expected value based on L. [25,31] This can be thought of as an increase in the effective value of L due to the increased probability of quasiparticle diffusion in the leads. Consequently, while E c ∼ 55 µeV for a length L = 450 nm and D = 170 cm 2 /s, we have used a value of 2.7 µeV, adjusting the values of ∆ and T which are specified in units of E c accordingly.…”
Section: Squidsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, this is for a wire with no additional normal metal leads. Experimentally, by measuring the saturation value of I c at low temperatures, we have found that E c is reduced by a fac-tor of about 20 from its expected value based on L. [25,31] This can be thought of as an increase in the effective value of L due to the increased probability of quasiparticle diffusion in the leads. Consequently, while E c ∼ 55 µeV for a length L = 450 nm and D = 170 cm 2 /s, we have used a value of 2.7 µeV, adjusting the values of ∆ and T which are specified in units of E c accordingly.…”
Section: Squidsmentioning
confidence: 81%
“…[25] Consequently, R 21,76 also shows a sharp drop at the same values of I b . As |I b | is increased further, both nonlocal differential resistances approach their normal state values (modulated by the current distribution of the quasiparticle currents), positive for R 21,35 and negative for R 21,76 , the difference in sign being due to the relative orientation of the their respective voltage leads.…”
mentioning
confidence: 87%
See 1 more Smart Citation